Usefulness of cerebrospinal fluid presepsin (soluble CD14 subtype) as a new marker in the diagnosis of neurosurgical postoperative meningitis - Fuchinoue, Yutaka; Kondo, Kosuke; Sakaeyama, Yuki; Nakada, Chie; Terazono, Sayaka; Kubota, Syuhei; Mikai, Masataka; Abe, Mituyoshi; Ujiie, Shinji; Morita, Toshisuke; Sugo, Nobuo (Frontiers in Neurology, 2024)
Objective To determine the usefulness of cerebrospinal fluid (CSF) presepsin in the diagnosis of neurosurgical postoperative meningitis (POM). Methods The study included patients admitted to the Department of Neurosurgery, Toho University Medical Center Omori Hospital from May 1, 2020 to March 31, 2022 with suspected meningitis after neurosurgery who clinically required CSF sampling and patients who underwent CSF sampling for examination of idiopathic normal pressure hydrocephalus (iNPH). Participants were divided into a POM and a postoperative non meningitis (PONM) group based on the POM diagnostic criteria established for this study. The control group included patients from whom a CSF sample for iNPH was collected by tap test. Results A total of 238 CSF samples were collected from 90 patients. There were 39 samples in the POM, 180 samples in the PONM, and 19 samples in the control group. CSF presepsin levels in the POM were significantly higher than in the PONM group (1764.5 and 440.9 pg./mL, respectively; p < 0.0001). The control group had CSF presepsin levels of 95.5 pg./mL. A cutoff value of 669 pg./mL for CSF presepsin in POM and PONM groups had 76.9% sensitivity and 78.3% specificity for the diagnosis of POM. In analyzes including only subarachnoid hemorrhage (SAH) cases (123 samples), CSF presepsin (1251.2 pg./mL) in the POM was significantly higher than in the PONM subgroup (453.9 pg./mL; p < 0.0001). The cutoff value for presepsin in CSF among patients with SAH (669 pg./mL) had 87.5% sensitivity and 76.6% specificity, similar to that of all patients. Conclusion CSF presepsin is a useful marker in the diagnosis of neurosurgical POM even in patients with blood components, such as SAH. When POM is suspected, measurement of CSF presepsin may be recommended in addition to a general CSF examination.